Investigations of associated multi-band observations for GEO space debris. Issue 10 (15th May 2017) - Lu, Yao; Zhang, Chen; Sun, Rong-yu; Zhao, Chang-yin; Xiong, Jian-ning
Abstract: According to the proposal of active space debris removal, the knowledge of the shape, rotational state and surface characteristics of space debris is demanding. An associated multi-band observation of the Geosynchronous Earth Orbit space debris is performed to investigate the improvement and promotion while infrared and g ′ Vr ′ i ′ information are provided. The Quad-Channel Telescope and the famous United Kingdom Infrared Telescope are adopted in our observation, along with other two dedicated space debris telescopes. Due to the limitation of geometry, the infrared data of 13 objects are acquired, and the photometry results are obtained. The tumbling motion is analyzed with the brightness variations, and the color indices are investigated according to the bus type of objects. At last the frequency analysis of the multi-band light curves is performed, the consistency and non-consistency of the results under different circumstances are presented. It is demonstrated that the adoption of multi-band observations is useful for increasing the knowledge of space debris, and the applications are deserved to be further promoted.